Corrosion resistance of in-situ growth of nano-sized Mg(OH)2 on micro-arc oxidized magnesium alloy AZ31—Influence of EDTA. Issue 6 (June 2019) - Li, Chang-Yang; Fan, Xiao-Li; Zeng, Rong-Chang; Cui, Lan-Yue; Li, Shuo-Qi; Zhang, Fen; He, Qing-Kun; Kannan, M. Bobby; Jiang, Hong-Wei (George); Chen, Dong-Chu; Guan, Shao-Kang
Abstract: One of the major obstacles for the clinical use of biodegradable magnesium (Mg)-based materials is their high corrosion rate. Micro-arc oxidation (MAO) coatings on Mg alloys provide mild corrosion protection owing to their porous structure. Hence, in this study a dense Mg(OH)2 film was fabricated on MAO-coated Mg alloy AZ31 in an alkaline electrolyte containing ethylenediamine tetraacetic acid disodium (EDTA-2Na) to reinforce the protection. Surface morphology, chemical composition and growth process of the MAO/Mg(OH)2 hybrid coating were examined using field-emission scanning electron microscopy, energy dispersive X-ray spectrometer, X-ray diffraction, X-ray photoelectron spectroscopy and Fourier transform infrared spectrophotometer. Corrosion resistance of the coatings was evaluated via potentiodynamic polarization curves and hydrogen evolution tests. Results manifested that the Mg(OH)2 coating possesses a porous nano-sized structure and completely seals the micro-pores and micro-cracks of the MAO coating. The intermetallic compound of AlMn phase in the substrate plays a key role in the growth of Mg(OH)2 film. The current density of Mg(OH)2 -MAO composite coating decreases three orders of magnitude in comparison with that of bare substrate, indicating excellent corrosion resistance. The Mg(OH)2 -MAO composite coating is beneficial to the formation of calcium phosphate corrosion products on the surface of Mg alloy AZ31, demonstrating a great promise for orthopaedic applications.